2013
DOI: 10.12659/msmbr.883822
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-induced cessation of embryonic development is reversed by γ-tocotrienol in mice

Abstract: BackgroundThis study aimed to evaluate the adverse effects of various doses of nicotine and protective effects of different concentrations of γ-tocotrienol (γ-TCT) on in vitro embryonic development and lipid peroxidation in mice.Material/MethodsA) Effects of various doses of nicotine on in vitro embryonic development: Female mice were treated with 1.0, 3.0, or 5.0 mg/kg/day nicotine for 7 consecutive days. Animals were superovulated, cohabited overnight, and sacrificed. Embryos were cultured in vitro. Plasma w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…Nic as an OS inducer has been well established in the previous studies [14,27,40,41]. This study has further confirmed the effects of Nic as an OS inducer, as shown in our data on the increase of OS markers level in the Nic group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nic as an OS inducer has been well established in the previous studies [14,27,40,41]. This study has further confirmed the effects of Nic as an OS inducer, as shown in our data on the increase of OS markers level in the Nic group.…”
Section: Discussionsupporting
confidence: 91%
“…A study by Mokhtar et al (2009), on the animal model showed that oral supplementation with tocotrienol increased success rate of hatched blastocyst formation [11]. Our previous studies have reported that tocotrienol was able to reverse the oxidative stress (OS) effects on pre-implantation mouse embryos induced by corticosterone [12,13] and fetal development and survivability [14].…”
Section: Introductionmentioning
confidence: 99%
“…The fetal thymus develops from GD 11.5 to birth32. An in vitro research has showed that nicotine can reduce the hatched blastocyst and impair embryo development33. Moreover, an experiment on the effect of nicotine in different gestation period on offspring proved that the effect was more significant during the second and third trimester, especially the third trimester3435.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been established that many factors are likely to influence the outcome of IVF, such as the adverse roles of nicotine [18] and the methods of preservation of frozen embryos [19], the effects of endometriosis on the results of IVF are currently controversial. Therefore, the aim of the present study was to retrospectively assess the efficacy of NC endometrial preparation for FET in women with severe endometriosis.…”
Section: Discussionmentioning
confidence: 99%